Review and analysis of the research program of the International Irrigation Management Institute - Levine, G. (International Irrigation Management Institute, 1992)
This paper attempts to evaluate IIMI?s past research programs for the purpose of improvement in the current and future programs. It starts by placing irrigation management research in its historical and institutional contexts by comparison to agricultural research, looks at the way IIMI conducts its research and then proceeds to evaluate the programs, with special emphasis on the results. It concludes with general and specific recommendations, and a brief section on implementation.